Pengembangan Automatic Feeder Pakan Ikan Menggunakan Microcontroller ESP8266 - Very Kusuma Pela; I Gede Juliana Eka Putra; I Gede Putu Krisna Juliharta (Primakara University, 2020)
The Internet of Thing (IoT) is a combination of the internet and ubiquitoscomputing which has the function of controlling various kinds of electronic goods remotely and can be connected to various kinds of sensors. Technology can be used for the problem of feeding fish automatically which can be monitored from the blink application based on Android and IOS. The materials used in this study are iron and household furniture as construction, Mcu Esp8266 Node, Arduino, Loadcell, ultrasonic sensors, Servo Motors, and DC Motors. Tools that are made to work automatically run provide feed at predetermined hours and measure feed feed based on weight determined with a distance of ejection of feed up to 1 meter, and can be monitored using the blynk application via a local wifi network to find out the feed has been stocked and the amount of feed available in the main shelter.